Academic stress and coping strategies of forst year IIUM medical students - Myint, Yi Yi; Tun, Ye; Muhammad, Siti Aesah @ Naznin (2014)
BACKGROUND: Medicine is generally perceived as very stressful course as compared to other courses. Previous studies have reported that pressure of a challenging academic curriculum is very stressful for first year medical students. High level of stress is a risk factor for a wide range of physical and mental health-related consequences.